(3GdJQHjI HGdYbGH (B:s (3HMK aj VhGHW GdYbGH GdJQHhj hGdeQahV efg hGdebHhd (B/s - (3OGQ GdCed ddWHY hGdfTQ hGdJhRjY (B((3eUQ(B).s (3GdaQjb GdYdej HOGQ GdCed (B.s; (3GdebOe, eMeO Hf CMeO Hf ESeGYjds 1952- ((3eUQ (B:s (3OGQ GdCed ddWHY hGdfTQ hGdJhRjY ,s, 2023)
(3gPG GdcJGH eMGhdI dGSJjYGH VhGHW GdYbGH GdJQHhj, hfhYjg GdebHhd hGdeQahV, hbO bOeJ Hjf jOj GdbGQF Pdc eONdG jVe JfHjgGJ JeS GdMGLI Edi HjGfgG ; aEf eYXe GdeTGcd GdJQHhjI JfTC ef fbU GdeYdheGJ, Ch ef GdeYdheGJ GdeZdhWI, aYOe GdYde Lgd, hGdNWC aj GdYde Lgd CjVG(B. (3hceG dG JOaY GdbeGT Edi ZjQ GdNjGW djNjWg, aChdi Cf jchf GdeQHj eDgdG ddJQHjI, hNGdjG ef ehGfY CgdjJgG GdJj CNWQgG GdLgd(B.s
Keywords: (3JQHjI ESdGejIs; (3GdKhGH hGdYbGH s